Processo de avaliação de princípios do Seis Sigma aplicados em empresas construtoras - Yamamoto, Lucio Schiavon (2021)
Although the civil construction sector has adopted management tools and methods for the production and quality control of services, there is still a gap in applying effective quality management. The problems occur in the control of documentation and the control of processes, products, and continuous improvement. This research aims to propose an evaluation structure for Six Sigma application through a structured questionnaire or checklist for construction companies. The checklist was developed from a systematic review of the literature in which the six principles of Six Sigma are most used in civil construction internationally. Then, case studies were carried out on construction sites, and the checklist was applied to ten construction companies to identify each one's strengths and weaknesses. The research was realized with the technical staff of the building's site and quality management. The results showed that the companies contacted, on average, have mastered the principle of "focus on end customers," however they still have some difficulty in the application of quality management tools. Besides, it was found that characteristics such as the application of audits, the company's size, the existence of a quality department, and the existence of quality certifications influence the scoring of the Six Sigma principles. Therefore, according to the sample, it is concluded that the civil construction industry needs to develop mechanisms to promote the management of continuous improvement, having as a guideline the implementation and maintenance of methods and quality controls. It was observed that construction companies must first reach a total quality control level for effective continuous improvement management.